The Influence of Political Factors on the Architecture of Ducal Castles Owned by the Griffin Dynasty - Jakub Ignacy Gołębiewski (Arts, 2020)
The subject of the article is an analysis of the ideological and political factors that influenced the architectural transformation of ducal residences which belonged to the Griffin dynasty during the Prussian-German and later Polish rule. The article verifies the scale of this impact and the formal effects of actions taken in the context of the entire Pomeranian Duchy. The research is based on a selected set of ducal castles from the Pomeranian region and uses analytical and comparative methods. In the course of the research, it was possible to confirm the influence of political and ideological factors on the status of the preserved heritage of the Pomeranian Dukes, both on the part of the Prussian-German and Polish authorities. In both cases, these actions were caused by the desire to take over symbolic control over the space after territorial changes. These actions were aimed either at eliminating elements foreign to a given nation and state from the cultural landscape of Pomerania or at their transformation and familiarization. In the process of transforming ducal castles, utility factors also played a significant role in the Prussian-German period, while after 1945 the important factor was the then conservation doctrine.